Intentions and influencing factors regarding natural childbirth among urban pregnant women in China, based on the theory of reasoned action and structural equation modeling. Issue 9 (September 2019) - He, Jingjing; Wan, Li; Luo, Biru
Objectives: In the present study, we aimed to analyze the status of natural childbirth and factors influencing delivery behaviors among pregnant women in urban areas based on the theory of reasoned action, to provide a basis for health education on natural childbirth. Methods: We recruited 658 pregnant women at West China Second University Hospital, Sichuan University. Using a literature review, expert consultation, and self-report questionnaires based on the theory of reasoned action, we investigated delivery behaviors and influencing factors among the included pregnant women. The questionnaires primarily comprised general situations and behavioral intentions regarding natural childbirth among pregnant women. The data were analyzed using IBM SPSS 21.0 software. Results: According to structural equation modeling, participants' behavioral intentions regarding natural childbirth were influenced by normative beliefs (standardized regression coefficient 0.402), outcome evaluation (standardized regression coefficient 0.123), and behavioral beliefs (standardized regression coefficient 0.316). Conformity motivation and knowledge about childbirth affected the choice of natural childbirth via normative beliefs (standardized regression coefficients 0.431 and 0.338, respectively). Conclusions: We found that the behavioral intentions of urban pregnant women with respect to natural childbirth were affected by normative beliefs, outcome evaluations, behavioral beliefs, conformity motivation, and knowledge about childbirth.